The effect of dobutamine on ocular blood flow of healthy adults: A 3D pseudocontinuous aterial spin labelling study - Cai, Linkun; Niu, Haijun; Ren, Pengling; Liu, Yawen; Zhang, Tingting; Liu, Dong; Zhao, Erwei; Zhu, Liang; Li, Jing; Qiao, Penggang; Zheng, Wei; Wang, Zhenchang (Frontiers in Physiology, 2022)
Purpose: Ocular blood flow (OBF) is an important risk factor for incidence, prevalence and progression of some ocular disorders. To date, there are very limited therapeutic options to increase OBF. This study investigate the effect of dobutamine on OBF of heathy adults using 3D pseudocontinuous arterial spin labelling (3D-pcASL), and explore the risk factors associated with OBF. Methods: Forty-three healthy participants (86 eyes) were given an intravenous injection of dobutamine. We measured OBF using 3D-pcASL with a 3.0T- MRI scanner, OBF values were independently obtained by two doctors from the OBF map. We also collected physiological parameters using a vital signs monitor. The OBF and physiological parameters in the in the period before and after dobutamine injection states were obtained. Results: OBF increased significantly after dobutamine injection using paired t test method (from 22.43±9.87 to 47.73±14.02 mL/min/100g, P<0.001). Age, heart rate and systolic blood pressure were the main risk factors affecting OBF using logistic regression analysis (all P values<0.05). Conclusion: To the best of our knowledge, this is the first study observing the effect of dobutamine on OBF. Our findings indicated that intravenously injected dobutamine increased OBF, making it a possible option to counteract ocular vascular ischaemia in the future.